PENGEMBANGAN MEDIA PEMBELAJARAN KOTA BERITA BERBANTUAN SMART APPS CREATOR 3 PADA MATERI TEKS BERITA SISWA KELAS VII SMP NEGERI 6 TANJUNGPINANG TAHUN AJARAN 2025/2026 - Rena Fitriani; Legi Elfitra; Fabio Testy Ariance Loren; Harry Andheska; Dody Irawan; Isnaini Leo Shanty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop the Kota Berita learning media on News Text Material for Grade VII Students of SMP Negeri 6 Tanjungpinang for the 2025/2026 Academic Year. The development model used in this study is the 4D model up to the development stage only. The media developed is in the form of interactive multimedia learning in the form of an application containing material, practice questions, and quizzes about news texts completed by students. Kota Berita media has been assessed by two validators, namely media experts and material experts. The number of students testing the practicality of the media was 5 for the small group and 40 for the large group. The data collection techniques in this study included interviews, media validation questionnaires by media experts and subject matter experts, as well as media practicality questionnaires by students consisting of large and small groups. The data analysis techniques in this study consisted of qualitative descriptive and quantitative descriptive analysis. The results of this study showed that the Kota Berita media obtained a validation percentage from media experts of 89% on average with a qualification of “highly valid”, while the validation from subject matter experts was 85% with a qualification of